Consumers' perceptions of community pharmacy in Portugal - Cavaco, AM (2015)
Objective: Pharmacists are health professionals who are ideally positioned to perform a primary health care role. However, the definition of professional value needs to be considered not just as professional education and skills, but also in terms of how consumers perceive it. The main aim of this work was to explore the public's perceptions and attitudes towards community pharmacy in Portugal. Methods: A pure qualitative approach was undertaken. The data were collected through a semi-structured interview, conducted with a 'snowball' like sample. First, individuals ( n = 15) were interviewed, allowing for adjustment and validation of the interview schedule, followed latter by group interviews with adults in rural and urban areas. Group participants ( n = 25) were asked about their behaviour and beliefs, resulting from their perceptions of community pharmacies, pharmacists and medicines. Future expectations regarding the community pharmacy service were also explored. The interviews were tape recorded and transcribed verbatim. An iterative, reflexive coding process was applied, assisted by the qualitative software package QSR NUD* IST v4. The inductive analysis of the extracted codes assembled those codes into themes. Results and discussion: This article will mainly focuses on community pharmacy service representations and cognitions ( theme A) and community pharmacy evaluative perceptions and behaviours ( theme B). Participants displayed general and contradictory ideas about the actual functions of the pharmacist, including weak conceptualizations and a positive demand for services in relation to product supply. This superficial understanding is in line with previous results from satisfaction studies, confirming a low expectation level. The public's poor knowledge and low expectations can justify a reduced desire for an extended role of the pharmacist in the community. This uncertain service conceptualization does not define the professional responsibility from a consumer's perspective. Conclusions: Although these results allow for the development of a framework to describe the perceptions of community pharmacy users, further research is needed to determine the prevalence of these and other possible results.